Seabird-vectored pelagic nutrients integrated into temperate intertidal rocky shores - Healing, Samuel; Benkwitt, Cassandra E.; Dunn, Ruth E.; Graham, Nicholas A. J. (Frontiers in Marine Science, 2024)
Seabirds provide inter-habitat connectivity by transporting vast quantities of nutrients from their pelagic feeding grounds to terrestrial and marine ecosystems via their nitrogen and phosphorous rich guano. However, it remains unclear whether seabird nutrients are cycling through many nearshore, temperate systems, such as United Kingdom (UK) rocky shores. Furthermore, it also remains unknown how seabird nutrient subsidies impact biodiversity, productivity, and recolonisation rates in UK rocky intertidal systems. Here, the impact of seabird nutrient subsidies to the Farne Islands, Northumberland, areas of high seabird densities during their breeding seasons, was compared to nearby low seabird density areas on the Northumberland coast. Estimated seabird derived nitrogen inputs and seabird densities were 420-1,025 and 949-2,279 times higher, respectively, on seabird islands than on the mainland. Seabird derived nutrient inputs led to substantially enriched nitrogen stable isotope (δ15N) values and total nitrogen content in terrestrial soil, plants, and lichen, and intertidal barnacles, and limpets, and higher δ15N values in macroalgae and turf algae. The seabird islands contained marginally greater algal species richness and higher densities of intertidal predators. However, other drivers could not be ruled out, such as nutrient inputs from mainland sources and marginally higher wave exposure at the mainland sites. No difference in limpet size, biomass, or abundance existed between the seabird islands and the mainland. On plots artificially cleared to simulate a disturbance event, barnacles recolonised faster on mainland sites. These findings provide evidence that seabird vectored pelagic nutrients are incorporated into terrestrial and intertidal ecosystems of UK islands, and therefore play an important role in facilitating ecosystem connectivity.